PENGAJARAN MISI BAGI JEMAAT KRISTEN DI ERA DIGITAL - Sandy Ariawan (Sekolah Tinggi Teologi Arastamar Bengkulu, 2025)
Missional education for Christian congregations faces new challenges and opportunities in the digital age, characterized by rapid advances in information and communication technologies. This article explores how churches can adapt their mission strategies to capitalize on digital technologies, while addressing the various challenges that arise. The research also addresses various important aspects, including the adaptation of the gospel message for various digital formats, coaching in building and maintaining online faith communities, as well as ethical principles that should be applied in digital interactions. The method used in this research is a literature study. The results show that mission education in the digital age requires adjustments and strategic thinking to optimize the potential of technology and overcome existing challenges, with the ultimate goal of strengthening the spread of the message of Christ and church development in the digital world. The main challenges identified include the limitations of personal interactions that often lack depth in online contexts, as well as security and privacy issues relating to the protection of congregational data and the authenticity of information. In addition, communication ethics and respect for privacy are important factors in ensuring accurate and ethical information dissemination.